2014
DOI: 10.1371/journal.pone.0094603
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Active Pulmonary Tuberculosis in Patients with Coincident Filarial and/or Intestinal Helminth Infections Followed Longitudinally in South India

Abstract: BackgroundFilarial (and other helminth) infections are known to modulate mycobacteria-specific pro-inflammatory cytokine responses necessary for maintaining latency in tuberculosis (TB). We sought to address whether helminth co-infection alters progression to active pulmonary TB in a co-endemic area of South India.Methods/Principal FindingsIncidence of active pulmonary TB was assessed in 5096 subjects from five villages among helminth-infected (hel+) and –uninfected (hel−) groups. Baseline stool examinations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…In a cross-sectional study in South India, a delayed-type-hypersensitivity response to purified protein derivative (PPD) was not affected by coincident intestinal helminth and/or filarial infections (32). Findings from another large-scale prospective study from the same geographical area demonstrated that there is no difference in the incidences of TB in helminth-infected and uninfected groups (33). Contrasting the above reports, several other studies have demonstrated that helminth coinfection has a negative impact on the outcome of M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 80%
“…In a cross-sectional study in South India, a delayed-type-hypersensitivity response to purified protein derivative (PPD) was not affected by coincident intestinal helminth and/or filarial infections (32). Findings from another large-scale prospective study from the same geographical area demonstrated that there is no difference in the incidences of TB in helminth-infected and uninfected groups (33). Contrasting the above reports, several other studies have demonstrated that helminth coinfection has a negative impact on the outcome of M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 80%
“…Further studies are now needed to investigate the impact on these Treg responses on progression to TB. Although a recent study in India failed to show any effect on the rate of progression to active TB associated with filaria or hookworm infections [48], reinfection with both helminths and M. tuberculosis would be common in this setting [49]. The next question that now needs to be answered is to understand how helminths induce this population of CD4 + FoxP3 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the effect of anthelmintic treatment on clinical outcomes (8,26) as well as on Mycobacterium bovis BCG vaccination (27,28) have yielded conflicting results. However, examination of T cell responses in helminth-infected individuals clearly showed diminished T cell proliferation and IFN-␥ production in response to purified protein derivative (PPD) and partial reversal of the diminished levels following albendazole therapy, although the LTB status of the population was not ascertained (29).…”
Section: Discussionmentioning
confidence: 99%
“…S. stercoralis infection is often clinically asymptomatic and longstanding due, in large part, to the parasites' autoinfective life cycle and their ability to modulate or evade the host immune system (2,7). Recent epidemiological and experimental data have provided evidence that helminths (both systemic and intestinal) have a negative regulatory role in the immune response to TB infection and disease, although no evidence exists for their having a significant impact on clinical outcomes of TB (1,8,9).…”
mentioning
confidence: 99%